PROFIL MOTIVASI BELAJAR SISWA KELAS VIII DI SMPN 2 CICALENGKA - Pathonah, Siti Hamdah; Wikanengsih; Rismawati Siddik, Riesa (IKIP Siliwangi, 2024)
The purpose of this researchis to provide an overview of the learning motivation of class VIII students at SMPN 2 Cicalengka. This study used a survey quantitative research method with data collection techniques in the form of a questionnairecontaining statements related to learning motivation given to 126 class VIII students at SMPN 2 Cicalengka as participants in this study. The results of the study revealed thatstudents' learning motivation was in the low category, namely as many as 86 students with a total percentage of 68%. As for the medium category, there are 35 students, which means around 28% of the total number. In the highcategory there are 5 students with a percentage of around 4%. Of the four components used to collect data, the component of students' positive thinking tendencies or optimism in learning is the component that has the lowest score among the other components of class VIII student motivation at SMPN 2 Cicalengka.